Avaliação da viabilidade econômica da produção de leite em sistemas pastoril e confinado, com a utilização do resíduo de sorgo sacarino como volumoso - Seiboth, Tânia Regina (2016)
The Brazilian agricultural sector constitutes itself as an important resource income for small producers all of whose manpower has been family character. The reduction of costs of the production process continues to make feasible the determining factor activity. For this it becomes necessary to verify the operational costs of production and analyze the factor which most impacts the costs of an enterprise of this nature. From this, it is necessary to think of a solution of working so as to integrate the production of energy and food. The objective of this study is to evaluate the economic viability of milk production in dairy cattle management systems pasture and confined in different scenarios related to animal feed, among which can highlight the determination of the integrated system of deployment of profitability of ethanol production and silage using sweet sorghum as raw material. In this study a quantitative approach was used. Realized the diagnosis of the dairy sector from the northwest region of the Rio Grande do Sul state (RS) through the withdrawals from analyzes performed by official bodies of the region (EMATER). The costs involved in the production of milk were provided obtained from the informal interviews in an intensive property that employs confined system and another system which uses intensive pasture. After assessing the costs held the integrated assessment of combustible ethanol production and silage for animal feed in a confined system. Diagnostic results of the show are positive and prospectus for growth. In relation to the production costs intensive pasture system presented a cost of R$ 0.72 per liter of milk produced, and the Intensive confined system has a cost of R$ 0.55 cents per liter. The economic analysis the two production systems are viable in the long run. About the integrated system, it is concluded it is a viable system and can increase the income of the small farmers. When analyzing the integrated production of ethanol and silage sweet sorghum and using the product in food, the profitability amounts to R$ 3.500,75 per hectare by employing confined system.